EFEKTIVITAS PESAN BAHAYA MEROKOK PADA BUNGKUS ROKOK TERHADAP PERILAKU PEKERJA STUDI DI NEGERI WAAI, KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Alex Robert Tutuhatunewa; Demsy Wattimena (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
Communication is a process of conveying a message from one person to another to tell about something, with the aim of changing attitudes, opinions and / or behavior. In the science of communication, persuasive communication is known, namely, communication carried out as an invitation or persuasion so that someone who receives the message (communicant) wants to act according to the wishes of the sender of the message (communicator). This study was conducted in relation to smoking habits in the community and the warnings about the dangers of smoking that were conveyed by the government through pictures and writing on each pack of cigarettes. In terms of communication, the government requires all cigarette manufacturers to put pictures and writings on cigarette packs, with the intention that the public is aware of the consequences of smoking that may be experienced by every smoker. The delivery of the message is expected to create public awareness to reduce and/or stop smoking. The problem of cigarettes has become a conversation in all circles of society, which raises the pros and cons of the existence of cigarettes. The development of cigarette consumption in Indonesia is no longer only among adults, but has penetrated into teenagers and even small children. On the basis of the problems mentioned above, this study was conducted with the aim of knowing whether the government's message about the dangers of smoking listed on cigarette packs is effective in changing people's behavior about cigarettes? By using the type of qualitative descriptive research, the researcher tries to describe, summarize, various conditions, and situations, on phenomena and/or social realities that exist in society. From the results of the study conducted, several things were found as follows: First, the public knew about the message about the dangers of smoking which was included on cigarette packs, but apparently the message was not able to influence people not to smoke and/or reduce smoking; Second, smoking has become a lifestyle (life style) and therefore, whatever the reason, it is difficult to expect much from awareness through messages about the effects of smoking on cigarette packs. Therefore, it is suggested that there should be an in-depth study and stricter regulation for someone in buying cigarettes.